An inverse optimization approach to inducing resource conservation in eco-industrial parks - Tan, Raymond Girard R. (Animo Repository, 2012)
The exchange of wastes among plants within an eco-industrial park (EIP) creates potential for significant gains in sustainability through efficient use of resources and reduction of environmental discharges. If the establishment of such resource conservation networks (RCNs) is not economically optimal, intervention of an EIP authority will be necessary in order to induce companies to act in an environmentally responsible manner. This conflict of interest between the EIP authority and the industrial plants results in a Stackelberg game, which may be represented as a bi-level optimization model. In this work, a bi-level linear integer programming model for optimizing waste exchange in an EIP is developed. Then, an inverse optimization approach is used to solve it. An auxiliary model is used to determine the best set of incentives and disincentives to induce the plants in the EIP to form an optimal RCN. The methodology is demonstrated using an illustrative case study. © 2012 Elsevier B.V.